THE CONTRIBUTION OF THE MEMBERS OF THE HOUSEHOLDS OF FISHERMEN IN INCREASING HOUSEHOLD INCOME OF FISHERMEN LABOUR JORONG PASIA TIKU NAGARI TIKU SELATAN TANJUNG MUTIARA SUBDISTRICT AGAM REGENCY OF WEST SUMATRA PROVINCE - Popy Meilia Tsani; Darwis Darwis; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe study was aimed to identify the types of activities or businesses undertaken by members of household fishermen, to know household income and to analyze the contribution of household members of fishermen. This research was conducted in April 2018 in Jorong Pasia Tiku Nagari Tiku Selatan Agam Regency. The research method used survey method. The respondents were collected by census in 40 KK. The result of the research shows that the income of laborers in Jorong Pasia Tiku is IDR1.767.625/ month. The fishermen's wife has job as salted fish farmer amounting to 12 people (30%), shellfish workers amounting to 2 people (5%), fried vendors there were 3 people (8%), traders were 20 people (50%) and food stalls were 3 people (8%). The average income of fishermen's wife in one month amounts to IDR801.000 / month. The fisherman's children have jobs as 8 fishermen (40%), shopkeepers 1 person (5%), fish dryers 2 people (10%), ojek drivers 3 people (15%), cell phone watchers 2 people (10%) and traveling traders numbered 3 people (15%). The average income of fishermen is IDR 1,092,500,- / month. The average household income of fishermen in 1 month amounted to IDR 3,112,375. Contribution of income given by fisherman is high (56,7%)and contributions to the members of the households of fishermen workers (wife and children) belongs to the medium (43,3%). Keyword: household, wife, kids, income, contribution